2012
DOI: 10.1007/s00405-012-2298-7
|View full text |Cite
|
Sign up to set email alerts
|

Endolymphatic sac tumors: experience of three cases

Abstract: ELST are difficult to diagnose due to the wide variety of their presentations. Patients with ELST should be screened for VHL disease. Dural invasion and tumor hypervascularization increase the risk of local recurrences after surgery. Early surgical resection may lead to complete tumor removal and inner ear preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…In general, the smaller the tumor at the time of removal, the lower the postoperative morbidity, where extensive surgery for much larger tumors is associated with disruption of the fallopian canal, jugular foramen, petrous apex, cerebrospinal fluid leak or involvement of the posterior cranial fossa, with concurrent loss of cranial nerve function (specifically VII, IX, and X) [29,33,38,57,58]. Thus, while many clinicians seem to eschew genetic counseling or testing in these patients, identification of the potential genetic relationship and removing the tumors at the earliest, and therefore smallest size possible, is advocated [5,31,33,57,58].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the smaller the tumor at the time of removal, the lower the postoperative morbidity, where extensive surgery for much larger tumors is associated with disruption of the fallopian canal, jugular foramen, petrous apex, cerebrospinal fluid leak or involvement of the posterior cranial fossa, with concurrent loss of cranial nerve function (specifically VII, IX, and X) [29,33,38,57,58]. Thus, while many clinicians seem to eschew genetic counseling or testing in these patients, identification of the potential genetic relationship and removing the tumors at the earliest, and therefore smallest size possible, is advocated [5,31,33,57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, we have to rule out intratumoral hemorrhage, which would disappear after 4 months on FLAIR, but contrasted T1 images would still show hyperintensity. Bastier et al 22 reported characteristic MRI imaging of 3 endolymphatic sac tumors, those are presence of cysts and spontaneous hemorrhage, hyperintense on T1-weighted images, hypointense bone spicules and flow void on T1- and T2-Weighted images, and heterogeneous enhancement after injection at MRI. Jeong et al also observed 9 patients of intralabyrinthine schwannoma can display characteristic MRI findings of a lack of normal fluid density on T2-weightd imaging, with corresponding enhancement observed on gadolinium-enhanced T1-weighted scans.…”
Section: Discussionmentioning
confidence: 99%
“…Its morphological features often seem to be benign, but locally invasive characteristic and destruction of the temporal bone disclose the low grade malignant nature of the tumor. ELSTs have a tendency to recur, but only two cases of metastasis have been reported and there has been no death. In this group of 10 cases, all of them had temporal bone destruction; five cases had recurrence and one of these cases recurred three times.…”
Section: Discussionmentioning
confidence: 99%